The Impact of AlN Templates on Strain Relaxation Mechanisms during the MOVPE Growth of UVB‐LED Structures. Issue 9 (27th May 2020) - Knauer, Arne; Mogilatenko, Anna; Weinrich, Jonas; Hagedorn, Sylvia; Walde, Sebastian; Kolbe, Tim; Cancellara, Leonardo; Weyers, Markus
Abstract: Strain relaxation mechanisms in AlGaN based light emitting diodes emitting in the ultraviolet B spectral range (UVB‐LEDs) grown on different AlN/sapphire templates are analyzed by combining in situ reflectivity and curvature data with transmission electron microscopy. In particular, the impact of dislocation density, surface morphology, and lattice constant of the AlN/sapphire templates is studied. For nonannealed AlN/templates with threading dislocation densities (TDDs) of 4 × 10 9 and 3 × 10 9 cm −2 and different surface morphologies strain relaxation takes place mostly by conventional ways, such as inclination of threading dislocation lines and formation of horizontal dislocation bands. In contrast, a TDD reduction down to 1 × 10 9 cm −2 as well as a reduction of the lattice constant of high temperature annealed AlN template leads to drastic changes in the structure of subsequently grown AlGaN layers, e.g., to transformation to helical dislocations and enhanced surface enlargement by formation of macrofacets. For the growth of strongly compressively strained AlGaN layers for UVB‐LEDs the relaxation mechanism is strongly influenced by the absolute values of TDD and the lattice constant of the AlN templates and is less influenced by their surface morphology. Abstract : UVB‐LED structures grown on different AlN/sapphire templates are analyzed by in situ reflectivity, curvature data, and transmission electron microscopy. This analysis suggests that for the growth of strongly compressively strained Al0.5 Ga0.5 N the relaxation mechanism is mostly influenced by the absolute values of threading dislocation density and the lattice constant of the AlN templates and is less influenced by their surface morphology.